2021
DOI: 10.1039/d1ra00253h
|View full text |Cite
|
Sign up to set email alerts
|

Fire extinguishing performance and mechanism for several typical dry water extinguishing agents

Abstract: Four new dry water fire extinguishing agents (FEAs) were developed by hydrophobic SiO2 and aqueous solution. Among them, dry water FEA with ammonium dihydrogen phosphate has the best extinguishing effect via temperature changes by thermocouples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This vapor again can cool down the temperature of the fire environment and also dilutes the oxygen (in the surroundings) finally leading to the suppression of fire. These facts are also considered in dry powder extinguishers 17,23,24 . However, the efficacy of materials is usually tested on a larger scale before practical utilization.…”
Section: Conceptualization and Development Of Fire Test Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…This vapor again can cool down the temperature of the fire environment and also dilutes the oxygen (in the surroundings) finally leading to the suppression of fire. These facts are also considered in dry powder extinguishers 17,23,24 . However, the efficacy of materials is usually tested on a larger scale before practical utilization.…”
Section: Conceptualization and Development Of Fire Test Setupmentioning
confidence: 99%
“…These facts are also considered in dry powder extinguishers. 17,23,24 However, the efficacy of materials is usually tested on a larger scale before practical utilization. As mentioned, all the tests require a larger volume of powder and water, and hence most of the time they remained as a limitation for screening.…”
Section: Conceptualization and Development Of Fire Test Setupmentioning
confidence: 99%
“…Another mechanism influencing the effective operation of extinguishing powders is the isolation of the fuel from the oxidant. This mechanism is characteristic of fire-extinguishing powders containing salts of phosphoric acid [18,19]. Such powders are particularly useful in extinguishing fires of solids forming glowing coals, classified as group A, which takes place during the combustion of materials of organic origin.…”
Section: Powder Extinguishing Agentsmentioning
confidence: 99%
“…Wang et al used four kinds of fire extinguishing agents to carry out solid and liquid fire extinguishing experiments. The results showed that the new dry water had the ability to extinguish fires of A, B, and C, and the cooling effect was superior to dry powder 10 . Liao explored the inhibition performance of dry water materials on starch cloud combustion.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the new dry water had the ability to extinguish fires of A, B, and C, and the cooling effect was superior to dry powder. 10 Liao explored the inhibition performance of dry water materials on starch cloud combustion. The research showed that the inert inhibition of dry water materials was mainly manifested by the vaporization and heat absorption of water in dry water materials and the heat insulation effect of hydrophobic phase nano silica.…”
mentioning
confidence: 99%